(untitled) (Research, Society and Development, 2020)
Wood has different uses, such as civil construction, furniture, cellulose pulp, and paper production, and energy generation. In this context, it is crucial to evaluate different wood properties in order to discover the potential for use in the wood segment. This research aimed to investigate the machining of Ingá wood (Inga edulis Mart). The analyzed wood was obtained from trees originated from thinning of the afforestation in public roads on the Seropédica campus of the Federal Rural University of Rio de Janeiro. For machining evaluation, a total of 10 specimens were produced and the degree of defects presented was analyzed, as well as the basic density of the wood. I. edulis wood showed satisfactory results for basic density and planing, sanding, vertical and horizontal drilling and nail cracking tests, and regular evaluation only for pin drilling. In this way, this research project studies the influence of machining tests on Inga edulis wood aiming at targeting it in diverse wood segments.